Molecular Epidemiology of Ampicillin-resistant Haemophilus influenzae Causing Acute Otitis Media in Japanese Infants and Young Children. Issue 5 (May 2016) - Kakuta, Risako; Yano, Hisakazu; Hidaka, Hiroshi; Kanamori, Hajime; Endo, Shiro; Ichimura, Sadahiro; Ogawa, Miho; Shimojima, Masahiro; Ozawa, Daiki; Inomata, Shinya; Tanouchi, Ayako; Kaku, Mitsuo; et al.
Abstract : Background: Nontypeable Haemophilus influenzae is a particularly important cause of acute otitis media (AOM). There is a high prevalence of β-lactamase–nonproducing ampicillin-resistant (BLNAR) strains in Japanese children, which is associated with recurrent AOM and prolonged treatment. The aim of this study was to investigate the antimicrobial susceptibility profile, mechanisms of ampicillin resistance and molecular epidemiology of ampicillin resistance in H. influenzae strains causing AOM in Japanese children. Methods: One hundred fifty-seven strains of H. influenzae isolated from the middle ear fluid of pediatric patients (aged 0–3 years) with AOM from various areas of Japan were studied. The antimicrobial susceptibility profile, genes encoding β-lactamase and alterations of penicillin-binding protein 3 were investigated. Genetic relatedness among ampicillin-resistant isolates was examined by multilocus sequence typing and pulsed-field gel electrophoresis. Results: Of 157 isolates, 108 (68.8%) demonstrated reduced susceptibility to ampicillin, including 95 (60.5%) of β-lactamase–nonproducing isolates and 13 (8.3%) of β-lactamase–producing isolates. All BLNAR (minimum inhibitory concentration of ampicillin ≥ 4 mg/L) isolates had amino acid substitutions related to ampicillin resistance. Multilocus sequence typing and pulsed-field gel electrophoresis demonstrated genetic diversity although there were 2 clusters of highly resistant isolates with identical STs (sequence types; ST161 and 549). Conclusions: Alterations of penicillin-binding protein 3 represented the most prevalent mechanism of ampicillin resistance among H. influenzae isolates causing AOM in Japanese children. BLNAR isolates from children with AOM demonstrated genetic diversity. This study identified for the first time ST clones associated with BLNAR H. influenzae causing AOM in Japanese children. Abstract : Supplemental Digital Content is available in the text.